Study of motor asymmetry in ALS indicates an effect of limb dominance on onset and spread of weakness, and an important role for upper motor neurons. Issue 7 (December 2014) - Devine, Matthew S.; Kiernan, Matthew C.; Heggie, Susan; McCombe, Pamela A.; Henderson, Robert D.
Abstract In amyotrophic lateral sclerosis (ALS), onset and spread of upper motor neuron (UMN) and lower motor neuron (LMN) dysfunction is typically asymmetric. Our aim was to investigate the relationship between limb dominance and the onset and spread of clinical UMN and LMN dysfunction in ALS. We studied 138 ALS subjects with unilateral and concordant limb dominance, from two tertiary centres. A questionnaire was used to determine the pattern of disease onset and spread. The clinical severity of UMN and LMN signs in each limb was quantified using a validated scoring system. Results showed that onset of weakness was more likely to occur in the dominant upper limb (p = 0.02). In subjects with initial weakness in a non-dominant limb, spread of weakness was more likely to be to the other limb on that side (p = 0.008). The relative distribution of upper limb UMN signs was affected by whether weakness first occurred on the dominant or non-dominant side (p = 0.03). These findings support limb dominance as a significant factor underlying onset and spread of ALS, with UMN processes playing an important role. The effect of limb dominance on the presentation of ALS may reflect underlying neuronal vulnerabilities, which become exposed by the disease.